Utility of cervical length and quantitative fetal fibronectin for predicting spontaneous preterm delivery among symptomatic nulliparous women. Issue 3 (19th April 2019) - Kyozuka, Hyo; Murata, Tsuyoshi; Sato, Tetsu; Suzuki, Satoshi; Yamaguchi, Akiko; Fujimori, Keiya
Abstract: Objective: To validate the utility of fetal fibronectin (fFN) and cervical length (CL) in predicting preterm delivery among symptomatic nulliparous women. Methods: A retrospective cohort study of nulliparous women who presented with uterine contractions, abdominal pain, or cervical change at 21–34 gestational weeks at Fukushima Medical University Hospital, Japan, between 2008 and 2017. fFN (categorized as <50 ng/dL, 50–199 ng/dL, >200 ng/dL) and CL (≥15 mm or <15 mm) were evaluated simultaneously. Adjusted odds ratios (aORs) and confidence intervals (CIs) for preterm delivery before 37 or 34 weeks, and delivery within 28 or 14 days were calculated (references: fFN, <50 ng/dL; CL, ≥15 mm). Result: Among 285 women who met the study criteria, CL less than 15 mm was a risk factor for preterm delivery before 37 (aOR, 4.1; 95% CI, 1.1–6.7) and 34 (aOR, 6.8; 95% CI, 2.3–20.2) weeks. fFN of 200 ng/dL or higher was a risk factor for delivery within 28 (aOR, 19.8; 95% CI, 4.3–90.2) and 14 (aOR, 10.8; 95% CI, 1.7–67.6) days. Conclusion: Among symptomatic nulliparous women, short CL was found to be a risk factor for preterm delivery and higher fFN levels were related to short gestational latency. Abstract : Among symptomatic nulliparous women, short CL was a risk factor for preterm delivery and higher fetal fibronectin levels were associated with short gestational latency.